determine a distancia entre os pontos :
a A(1,3 ) e B(5,7) c E(11,7) e F (3,1)
b C ( -1,5)e D(11,0) d G(-12,-7) e H(8,8)
Respostas
respondido por:
0
usando Pitágoras ficará assim: (xa-xb)²+(ya-yb)²=distancia²
a (1-5)²+(3-7)²=d² -4²+-4²=d² 16+16=d² d== 2
b (-1-11)²+(5-0)²=d² 144+25=d² d= d=13
c (11-3)²+(7-1)²=d² 64+36=d² d= d=10
d (-12-8)²+(-7-8)²=d² 400+225=d² d= d=25
a (1-5)²+(3-7)²=d² -4²+-4²=d² 16+16=d² d== 2
b (-1-11)²+(5-0)²=d² 144+25=d² d= d=13
c (11-3)²+(7-1)²=d² 64+36=d² d= d=10
d (-12-8)²+(-7-8)²=d² 400+225=d² d= d=25
respondido por:
1
(a) d(A,B) = √ (x2 - x1)² + (y2 - y1)²
d(A,B) = √ (5 - 1)² + (7 - 3)²
d(A,B) = √ 4² + 4²
d(A,B) = √ 16 + 16
d(A,B) = √32
d(A,B) = √ 2²-2².2
d(A,B) = 2.2√2
d(A,B) = 4√2
(b) d(C,D) = √ (x2 - x1)² + (y2 - y1)²
d(C,D) = √ (11 - (-1) )² + (0 -5)²
d(C,D) = √ (11 + 1)² + (-5)²
d(C,D) = √ 12² + (-5)²
d(C,D) = √ 144 + 25
d(C,D) = √ 169
d(C,D) = 13
(c) d(E,F) = √ (x2 - x1)² + (y2 - y1)²
d(E,F) = √ (3 - 11)² + (1 - 7)²
d(E,F) = √ (-8)² + (-6)²
d(E,F) = √ 64 + 36
d(E,F) = √ 100
d(E,F) = 10
(d) d(G,H) = √ (x2 - x1)² + (y2 - y1)²
d(G,H) = √ (8 - (-12) )² + ( 8 - (-7) )²
d(G,H) = √ (8 + 12)² + (8 + 7)²
d(G,H) = √ (20)² + (15)²
d(G,H) = √ 400 + 225
d(G,H) = √ 625
d(G,H) = 25
d(A,B) = √ (5 - 1)² + (7 - 3)²
d(A,B) = √ 4² + 4²
d(A,B) = √ 16 + 16
d(A,B) = √32
d(A,B) = √ 2²-2².2
d(A,B) = 2.2√2
d(A,B) = 4√2
(b) d(C,D) = √ (x2 - x1)² + (y2 - y1)²
d(C,D) = √ (11 - (-1) )² + (0 -5)²
d(C,D) = √ (11 + 1)² + (-5)²
d(C,D) = √ 12² + (-5)²
d(C,D) = √ 144 + 25
d(C,D) = √ 169
d(C,D) = 13
(c) d(E,F) = √ (x2 - x1)² + (y2 - y1)²
d(E,F) = √ (3 - 11)² + (1 - 7)²
d(E,F) = √ (-8)² + (-6)²
d(E,F) = √ 64 + 36
d(E,F) = √ 100
d(E,F) = 10
(d) d(G,H) = √ (x2 - x1)² + (y2 - y1)²
d(G,H) = √ (8 - (-12) )² + ( 8 - (-7) )²
d(G,H) = √ (8 + 12)² + (8 + 7)²
d(G,H) = √ (20)² + (15)²
d(G,H) = √ 400 + 225
d(G,H) = √ 625
d(G,H) = 25
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás